St. James's Hospital and Lucas Engineering Systems Ltd - A public/private sector collaboration in BPR project B - The re-organisation of purchasing and supplies - Bence, Valerie (Cranfield School of Management, 1995)
This Working Paper is the second in a series of three examining Business Process Re¬design (BPR) within the National Health Service (NHS). Together with Manuscript 12a it examines an innovative collaboration in BPR between St James's Hospital, Leeds and Lucas Engineering Systems Ltd (LES). These two organisations (one public sector and one private) worked together to design and implement what are essentially manufacturing methodologies to within an NHS hospital, already undergoing huge changes.